In vitro activity of tigecycline and comparators against carbapenem-susceptible and resistant Acinetobacter baumannii clinical isolates in Italy - Carattoli Alessandra; Nicolosi Daria; Nicolosi Vito; Gona Floriana; Trovato Giusi; Mezzatesta Maria; Fadda Giovanni; Nicoletti Giuseppe; Stefani Stefania (BMC, 2008)
Abstract Background In a recent multi-centre Italian survey (2003-2004), conducted in 45 laboratories throughout Italy with the aim of monitoring microorganisms responsible for severe infections and their antibiotic resistance, Acinetobacter baumannii was isolated from various wards of 9 hospitals as one of the most frequent pathogens. One hundred and seven clinically significant strains of A. baumannii isolates were included in this study to determine the in vitro activity of tigecycline and comparator agents. Methods Tests for the susceptibility to antibiotics were performed by the broth microdilution method as recommended by CLSI guidelines. The following antibiotics were tested: aztreonam, piperacillin/tazobactam, ampicillin/sulbactam, ceftazidime, cefepime, imipenem, meropenem tetracycline, doxycycline, tigecycline, gentamicin, amikacin, ciprofloxacin, colistin, and trimethoprim/sulphametoxazole. The PCR assay was used to determine the presence of OXA, VIM, or IMP genes in the carbapenem resistant strains. Results A. baumannii showed widespread resistance to ceftazidime, ciprofloxacin and aztreonam in more than 90% of the strains; resistance to imipenem and meropenem was 50 and 59% respectively, amikacin and gentamicin were both active against about 30% of the strains and colistin about 99%, with only one strain resistant. By comparison with tetracyclines, tigecycline and doxycycline showed a higher activity. In particular, tigecycline showed a MIC90 value of 2 mg/L and our strains displayed a unimodal distribution of susceptibility being indistinctly active against carbapenem-susceptible and resistant strains, these latter possessed OXA-type variant enzymes. Conclusion In conclusion, tigecycline had a good activity against the MDR A. baumannii strains while maintaining the same MIC90 of 2 mg/L against the carbapenem-resistant strains.